2013
DOI: 10.1007/978-3-642-38718-0_7
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Two-Level Preconditioned Conjugate Gradient Method on the GPU

Abstract: Abstract. We present an implementation of a Two-Level Preconditioned Conjugate Gradient Method for the GPU. We investigate a Truncated Neumann Series based preconditioner in combination with deflation. This combination exhibits fine-grain parallelism and hence we gain considerably in execution time when compared with a similar implementation on the CPU. Its numerical performance is comparable to the Block Incomplete Cholesky approach. Our method provides a speedup of up to 16 for a system of one million unknow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Since the system matrix is very ill conditioned, the use of preconditioners is required to achieve convergence at acceptable computation times. In this work we implement the Preconditioned Conjugated Gradients (PCG) solver in GPU using two types of suitable preconditioners to parallelize: diagonal scaling (Jacobi's preconditioner) and a Truncated Neumann Series based preconditioner [23]. Designated respectively as D and T N, in each case the preconditioning matrix looks like:…”
Section: Flow Equationmentioning
confidence: 99%
“…Since the system matrix is very ill conditioned, the use of preconditioners is required to achieve convergence at acceptable computation times. In this work we implement the Preconditioned Conjugated Gradients (PCG) solver in GPU using two types of suitable preconditioners to parallelize: diagonal scaling (Jacobi's preconditioner) and a Truncated Neumann Series based preconditioner [23]. Designated respectively as D and T N, in each case the preconditioning matrix looks like:…”
Section: Flow Equationmentioning
confidence: 99%
“…We have been investigating, [1], the idea of Two Level Preconditioned Conjugate Gradient method on GPUs starting with a simple problem and testing our preconditioning schemes and deflation on it. We have found that it is possible to efficiently map the deflation operation onto the GPU so that most of the fine-grain parallelism can be exploited on it.…”
Section: A Focus Of This Workmentioning
confidence: 99%
“…We consider a variety of first‐level preconditioning techniques along with deflation for a two‐level preconditioned conjugate gradient (PCG) implementation.…”
Section: Introductionmentioning
confidence: 99%
“…However, in this approach, incomplete Cholesky preconditioning is a bottleneck in a GPU implementation of the DPCG method. An implementation of the DPCG method on the GPU with a preconditioner exhibiting fine‐grained parallelism was first reported in , and better variants of deflation vectors were studied in . Both these works implemented DPCG on the GPU.…”
Section: Introductionmentioning
confidence: 99%